Small animals’ vital signs monitoring: development of an integrated system for preclinical PET systems - Oliveira, Regina Gapo de (2023)
The use of small animals in the preclinical research field has been very important to the investigation and development of diagnostic and treatment agents, as new drugs, action mechanisms of certain pathogenic agents, and the discovery of some deseases’ origin. In order to understand the organismtriggered responses to the referred processes, techniques and functional imaging systems, like Positron Emission Tomography (PET), are widely used. To perform the imaging procedures, mice have to be anesthetized, which can lead to changes in their physiological parameters and vital signs. Thus, this work has as main goal the development of a system for monitoring the mice’ vital signs in real time, during PET imaging procedures, performed with easyPET system, in order to ensure the animals well-being over the imaging acquisition. The considered vital signs were: heart rate, respiratory rate, oxygen saturation, and body temperature. This study evaluates a set of sensors (piezoelectric sensor, optical module, non-invasive ECG, and thermistor) for the different animal’s vital parameters measurement, of which stands out the developed hardware, as well as the software necessary to control the several devices. The several sensors were tested, at an initial phase, in human volunteers, being later implemented in the bed prototype, which as been also tested in a real application, with mice. In order to test the developed system, the mice were submitted to different anesthesias, in order to validate the system, through the comparison of the obtained values with ones well established in literature, for a similar anesthesia, and the system was also tested in an unknown situation. In the system validation phase, the mice were anesthetized with sevoflurane, and the obtained values where compared to the ones from isoflurane. Thus, at a sevoflurane’s concentration of 1.5%, the computed values to the heart rate were around the 388 bpm, the respiratory rate was about 124 rpm, and the SpO₂ was 88.9%. These values are considered coherent, since they are very close to the ones established for isoflurane. The system was also tested with an injectable anesthesia (ketamine+ chlorpromazine), which does not have reported values for the vital signs. In this case, the obtained values for the heart rate were between 321 and 383 bpm, for the respiratory rate varied from 182 to 226 rpm, and the SpO₂ was above 82%.